A global green new deal : rethinking the economic recovery - Barbier, Edward, 1957- (Cambridge : Cambridge University Press, 2010)
Meeting the short run challenges of reviving the worldwide economy need not mean sacrificing long run economic and environmental sustainability. A Global Green New Deal (GGND) is an economic policy strategy for ensuring a more economically and environmentally sustainable world economic recovery. Reviving growth and creating jobs should be essential objectives. But policies should also aim to reduce carbon dependency, protect ecosystems and water resources, and alleviate poverty. Otherwise, economic recovery today will do little to avoid future economic and environmental crises. Part One argues why a GGND strategy is essential to the sustainability of the global economy. Part Two provides an overview of the key national policies whilst Part Three focuses on the global actions necessary to allow national policies to work. Part Four summarizes the main recommendations for national and international action, and discusses the wider implications for restructuring the world economy towards 'greener' development.
Machine generated contents note: List of figures; List of tables; List of boxes; Author's preface; Acknowledgements; Foreword; Part I. Why a Global Green New Deal?: 1. Introduction: opportunity from crisis; Part II. The Key Components of a Global Green New Deal: 2. Reducing carbon dependency; 3. Reducing ecological scarcity; 4. Challenges facing developing economies; 5. National priorities for a global green new deal; Part III. The Role of the International Community: 6. Promoting global governance; 7. Facilitating access to finance; 8. Enhancing trade incentives; 9. Conclusion: international priorities for a global green new deal; Part IV. Towards a Greener World Economy: 10. Summary of recommendations; 11. Will a global green new deal succeed?; 12. Beyond a green economic recovery; Appendices; Glossary.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Sustainable development -- Government policy; Globalization